A monoclonal antibody with broad specificity for the ligands of insulin B:9-23 reactive T cells prevents spontaneous type 1 diabetes in mice. Issue 1 (1st January 2020) - Cepeda, Joseph Ray; Sekhar, Nitin S; Han, Junying; Xiong, Wei; Zhang, Ningyan; Yu, Liping; Dai, Shaodong; Davidson, Howard W.; Kappler, John W.; An, Zhiqiang; Zhang, Li
ABSTRACT: Activation of T cells specific for insulin B chain amino acids 9 to 23 (B:9–23) is essential for the initiation of type 1 diabetes (T1D) in non-obese diabetic mice. We previously reported that peptide/MHC complexes containing optimized B:9–23 mimotopes can activate most insulin-reactive pathogenic T cells. A monoclonal antibody (mAb287) targeting these complexes prevented disease in 30–50% of treated animals (compared to 10% of animals given an isotype control). The incomplete protection is likely due to the relatively low affinity of the antibody for its ligand and limited specificity. Here, we report an enhanced reagent, mAb757, with improved specificity, affinity, and efficacy in modulating T1D. Importantly, mAb757 bound with nanomolar affinity to agonists of both "type A" and "type B" cells and suppressed "type B" cells more efficiently than mAb287. When given weekly starting at 4 weeks of age, mAb757 protected 70% of treated mice from developing T1D for at least 35 weeks, while mAb287 only delayed disease in 25% of animals under the same conditions. Consistent with its higher affinity, mAb757 was also able to stain antigen-presenting cells loaded with B:9–23 mimotopes in vivo . We conclude that monoclonal antibodies that can block the presentation of pathogenic T cell receptor epitopes are viable candidates for antigen-specific immunotherapy for T1D.